Meta-analytic investigations of the effect of cognitive offloading on memory-based task performance and interindividual variability. - Burnett, Lois K.; Richmond, Lauren L. (Memory & Cognition, 2026)
Humans have long used external resources to overcome limitations of internal memory. However, experimental research investigating the efficacy of these strategies has emerged relatively recently. Given the rapidly growing interest in this topic, we conducted two meta-analyses to answer key questions regarding the effects of cognitive offloading – the use of physical action to reduce internal cognitive demand – on the performance of memory-based tasks. A meta-analysis of mean differences revealed that the benefit of offloading is greater for forced- compared to choice-offloading conditions and within- compared to between-subject designs. A meta-analysis of variance found that cognitive offloading reduces interindividual variability in the performance of memory-based tasks and that the reduction is greater for adults compared to children, for forced- compared to choice-offloading conditions, and for prospective compared to retrospective memory tasks. Study modality was not a significant moderator in either analysis. We discuss the applied, theoretical, and methodological implications of these findings.